Problems of Translating Nigerian Authors: The Case of Chinua Achebe’s No Longer at Ease - Ozulu, Ngozi (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1992)
AbstractEffort was made to identify some specific problems involved in translating Nigerian authors, with Chinua Achebe’s No Longer at Ease as a case study. It was discovered that the translation of some terms or phrases were inadequately rendered in French due to the problem of creating a suitably Africanized French stylistically, semantically, and pragmatically equivalent to its Anglophone counterpart. Hence, the problems encountered and identified were the peculiarity of Nigerian English, aspectual problems and non-uniformity in the orthography of Nigerian Pidgin and of course the existence of regionalized and africanized terms or Africanisms which have not found their ways into the dictionaries.